Measurement of Genetic Parameters Within and Between Haimen Chicken Populations Using Microsatellite Markers - Olowofeso, O.; Wang, J.Y.; Dai, G.J.; Yang, Y.; Mekki, D.M.; Musa, H.H. (International Journal of Poultry Science, 2005)
A total of 240 genomic DNAs were isolated from the four Haimen chicken populations: Rugao, Jiangchun, Wan-Nan and Cshiqishi, through a saturated salt procedure. The samples were used in a polymerase chain reaction (PCR) with 15 microsatellite markers. Amplified PCR-products with the markers were separated on a 12% polyacrylamide gel. Genetic parameters measured included allele number within locus per population, mean allele number across populations, mean allele number among loci for each population, effective allele number for each locus, mean across populations and among loci effective number of alleles (). Polymorphism information content (PIC) per locus and for all loci obtained as well as the average heterozygosity (H) among loci in the populations. The mean allele number for all loci ranged between 5.73±0.85 (Cshiqishi) to 6.00±0.74 (Rugao) and 6.00±0.84 (Jiangchun) with across populations for all loci equals 5.88±0.06; while (H) ranged from 0.6486±0.06 (Wan-Nan) to 0.7017±0.03 (Jiangchun) among loci and across populations, (H) was 0.6828±0.01. The () ranged from 3.96±0.60 (Wan-Nan) to 4.11±0.47 (Rugao); and () have values between 0.6068±0.06 (Wan-Nan) to 0.6509±0.04 (Jiangchun). The average heterozygosity among loci in each population was used further to obtained the cumulative power of discrimination (CPD) and was 99%. Angular genetic distances (DA) calculated ranged between 0.1691 (Rugao vs Wan-Nan) to 0.3372 (Rugao vs Cshiqishi). Dendrogram developed linked Rugao and Jiangchun as closely related, Wan-Nan been intermediate and Cshiqishi distantly related. It was concluded that the markers were suitable for the measurement of all genetic parameters of Haimen chicken populations.